Non-marine Chersodromia Walker from Southeast Asia and Papua New Guinea (Diptera, Empidoidea, Hybotidae) - Grootaert, Patrick; Cumming, Jeffrey; Shamshev, Igor (Zootaxa, 2007)
Two small species of Chersodromia Walker are described from lowland rain forest in Papua New Guinea and Thailand: C. flavicaput sp. nov. (Papua New Guinea, Thailand) and C. obscura sp. nov. (Thailand). The species are almost completely white, except for the contrastingly black eyes. Although the eyes touching on the face and wing venation suggest affinities with Nanodromia Grootaert, the extended gena, bristling on the apical half of the hind tibia and structure of the male genitalia indicate inclusion in Chersodromia. The new species represent the first non-marine Chersodromia reported from Southeast Asia and Papua New Guinea.